Design-Based Research (DBR): Integrasi Teori dan Praktik dalam Pengembangan Inovasi Pendidikan - Dedy Ismail; Guntur Guntur; Siti Badriyah (Jurnal Desain Indonesia., 2026)
Design-Based Research (DBR) has emerged as a significant research paradigm to bridge the gap between theory and practice in educational innovation. This study employs a critical literature review to analyze the application of DBR in the context of educational product development, with a focus on Indonesia. The findings reveal that DBR offers a contextual, iterative, and collaborative approach, contrasting sharply with conventional linear design models. Key outcomes of DBR include not only practical educational products but also actionable design principles and contextual theories. The study identifies seven core characteristics of DBR: iterative processes, theory-practice integration, interdisciplinary collaboration, dual outputs (products and principles), continuous validation, a focus on underlying mechanisms, and professional reflection. In the Indonesian context, DBR facilitates the integration of local wisdom and cultural values into educational innovations, promoting sustainability and relevance. However, challenges such as resource intensity, power imbalances in collaboration, and methodological complexity remain. The study concludes with practical implications for policy, practice, and further research, advocating for DBR as a transformative methodology for developing context-sensitive educational innovations in diverse settings like Indonesia.